Validity and usability testing of a health systems guidance appraisal tool, the AGREE-HS (2018)
ABSTRACT: Background: Health systems guidance (HSG) provides recommendations to address health systems challenges. No tools exist to inform HSG developers and users about the components of high quality HSG and to differentiate between HSG of varying quality. In response, we developed a tool to assist with the development, reporting and appraisal of HSG – the Appraisal of Guidelines for Research and Evaluation–Health Systems (AGREE-HS). This paper reports on the validity, usability and initial measurement properties of the AGREE-HS. Methods: To establish face validity (Study 1), stakeholders completed a survey about the AGREE-HS and provided feedback on its content and structure. Revisions to the tool were made in response. To establish usability (Study 2), the revised tool was applied to 85 HSG documents and the appraisers provided feedback about their experiences via an online survey. An initial test of the revised tool’s measurement properties, including internal consistency, inter-rater reliability and criterion validity, was conducted. Additional revisions to the tool were made in response. Results: In Study 1, the AGREE-HS Overview, User Manual, quality item content and structure, and overall assessment questions were rated favourably. Participants indicated that the AGREE-HS would be useful, feasible to use, and that they would apply it in their context. In Study 2, participants indicated that the quality items were easy to understand and apply, and the User Manual, usefulness and usability of the tool were rated favourably. Study 2 participants also indicated intentions to use the AGREE-HS. Conclusions: The AGREE-HS comprises a User Manual, five quality items and two overall assessment questions. It is available at agreetrust.org.